Effect of core strength training program on anaerobic power, speed and static balance in volleyball players - Bora, H.; Daglioglu, Ö. (European Journal of Physical Education and Sport Science, 2022)
The aim of this study is to examine the effect of the core strength training program applied to volleyball players on anaerobic power, speed and static balance. A total of 18 male volleyball players between the ages of 18-22, who regularly practice volleyball, participated in our study voluntarily. The subjects were divided into two different groups as the experimental group (n=9, age: 19.41±2.48) and the control group (n=9, age: 21.12±2.32). The control group continued their normal volleyball training. In the experimental group, in addition to volleyball training, a core strength training program was applied 3 days a week for 6 weeks. Core exercises are known as Mountain Climbers, Bicycle Crunch, Leg Raises, Russian Twist, Side Plank, Bridge, Abdominal Crunch, Jack Knife, Superman, Plank Jack were performed on the experimental group. Static balance scores were measured with the Biodex Balance System balance test device. A speed test (30 m) was applied. Anaerobic power was measured with the vertical jump test. Independent Samples T-Test was used for statistical evaluation between the experimental and control groups. Paired Samples T-Test was used for in-group comparisons. After the core training program was applied to the experimental group, significance was determined in the speed, anaerobic power and static balance scores (p<0.05). There was a significant difference between the groups in speed, anaerobic power and static balance scores in favor of the experimental group (p<0.05). As a result, it can be said that the core strength training program applied to volleyball players has a positive effect on speed, anaerobic power and static balance scores.